PERANCANGAN IKLAN LAYANAN MASYARAKAT TENTANG CARA MENGURANGI DAMPAK PEMANASAN GLOBAL DALAM MEDIA AUDIO VISUAL - BUDI MULYADI, Drs. Syafwan, M.Si, Dra. Zubaidah, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Global warming, where’s the temperature of the earth are extremely raising due to the emitions of human activity, is destroy the structure of the atmosphere. There for global warming should see as a serious problem, because it deals with human life. Nowaday people could get information with very easy and fast trough internet, smartphone or any othercommunication tool. Thus, the campaign of reducing affect of global warming will be served into form of audio visual.Keywords: Global warming, Effective, Audio Visual